Curriculum Development to Build the Character and Skills of Students in Pesantren - Siregar, Irma Suryani; Dalimunthe, Irwan Saleh; Darma, Satria (IAIN Ponorogo, 2024)
This study explores the curriculum development at Pesantren. This study focuses on Mushtofawiyah Pesantren. The pesantren faces significant challenges in integrating religious education based on the yellow book, which constitutes 80% of the curriculum, with general subjects allocated at 20%. This research employed a qualitative case study method. Data collection techniques were in-depth interviews, participant observation, and documentation studies. Then, the data were analyzed using the Miles, Huberman & Saldana model. Data validity was checked through triangulation by comparing data from various sources. The results indicate that the curriculum management at Mushtofawiyah Pesantren successfully creates a synergy between religious and general education despite challenges such as internal resistance and limited facilities. The success of the alumni, who now play prominent roles in various public and professional sectors, along with the strength of the alumni organization network, underscores the effectiveness of the educational model implemented. These findings offer valuable insights into how pesantren can adapt and remain relevant amid changing times without losing their religious identity.